DEVELOPMENT OF HPLC AND CHEMOMETRIC ASSISTED SPECTROPHOTOMETRIC METHODS FOR THE SIMULTANEOUS DETERMINATION OF FIVE ACTIVE INGREDIENTS IN COUGH AND COLD TABLETS AND THEIR APPLICATION TO DISSOLUTION STUDY - Bhamre, Prachi R.; Rajput, Sadhana J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Chemometric assisted spectrophotometry, and HPLC methods have been developed for the simultaneous determination of phenylephrine hydrochloride (PEPH), paracetamol (PCM), guaifenesin (GNF), chlorpheniramine maleate (CPM) and bromhexine hydrochloride (BRM). Methods: The chromatographic separation was carried out on a Phenomenex RPC18 column. An isocratic elution was carried out with the mobile phase comprising methanol, acetonitrile and 10 mM phosphate buffer (pH 3) in the ratio of 27.5:22.5:50 respectively at a wavelength of 218 nm. Two chemometric methods i.e. principal component regression (PCR) method and partial least squares (PLS) method were also developed to quantify each drug in the mixture using the information included in the UV absorption spectra of appropriate solutions in the range 210â€“320 nm with the intervals of 2 nm at 51 wavelengths. Results: The three methods were successfully applied to a tablet formulation and the results were compared statistically by applying ANOVA, which showed no significant difference among the three methods. The methods were applied to the dissolution study of the five components in tablet formulation and the percentage release of all the five components was found to be greater than 85% within 45 min by all the three methods. Conclusion: Thus, the proposed methods, i.e., PLS, PCR and HPLC, were found to be suitable and can be successfully used for the determination of the PEPH, PCM, GNF, CPM and BRM in pharmaceutical tablet formulation as well as for dissolution study. Â 